2015
DOI: 10.1002/ccd.26127
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery embolism from infectious endocarditis treated with catheter thrombectomy using a GuideLiner catheter

Abstract: A 27-year-old male with history of IV drug use and recurrent endocarditis necessitating bioprosthetic mitral and tricuspid valve replacements presented with 2 weeks of fevers and chest pain. ECG revealed inferior ST-elevation myocardial infarction and he was taken urgently to the cardiac catheterization laboratory. Coronary angiography revealed thrombotic occlusion of the distal right coronary artery (RCA) with no angiographic evidence of atherosclerotic disease. Aspiration thrombectomy was performed followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Embolic events occur after a median time of 7 days following the start of adequate antibiotic therapy (15), and 65-71.4% of cases, occur within ~2 weeks (15,16). Certain organ arterial emboli in infective endocarditis can cause lethal and/or severe outcomes (17)(18)(19). In the present case, the hepatic artery embolic event occurred in the second week after starting antibiotic treatment.…”
Section: Sle Causes Chronic Inflammation In Multiple Organs (8)mentioning
confidence: 63%
“…Embolic events occur after a median time of 7 days following the start of adequate antibiotic therapy (15), and 65-71.4% of cases, occur within ~2 weeks (15,16). Certain organ arterial emboli in infective endocarditis can cause lethal and/or severe outcomes (17)(18)(19). In the present case, the hepatic artery embolic event occurred in the second week after starting antibiotic treatment.…”
Section: Sle Causes Chronic Inflammation In Multiple Organs (8)mentioning
confidence: 63%
“…12 Several case reports and small case series describe coronary embolism as a complication of infective endocarditis. 8,10,[13][14][15] A review found that a murmur was present in almost 90% of cases. 8 In a case series, 13 of 14 patients had moderate to severe valvular regurgitation on echocardiography.…”
Section: ■ Septic Coronary Embolizationmentioning
confidence: 99%